Agenda of commitments to Comprehensive Health and Infant mortality in a city of Alagoas - Lidiane Moura Carvalhal; Danielly Santos dos Anjos; Célia Alves Rozendo; Laís de Miranda Crispim Costa (Universidade de Fortaleza, 2014)
Objective: To analyze health actions performed by nurses enrolled in the family health teams based on the Commitment Schedule to Child Integral Health and Infant Mortality Reduction. Methods: This is a quantitative exploratory-descriptive research, performed in a city of Alagoas, which used as instrument for data collection a checklist form, applied in the period from September to November 2012, covering the priority actions in primary care that contribute to the quality of prenatal care: good assistance to childbirth, puerperium and newborn. Data on the actions performed by nurses in the Family Health Strategy - FHS was analyzed grouped by their area of competence, organized, tabulated and presented in the form of table and graphs. Results: The participants were seven nurses of Family Health Teams, totaling 87.5% of the coverage in the municipality, being mostly female, between 31-35 years, in temporary job, with working time ranging from 3 to 4 years. The development of actions by nurses relating healthcare and education and aiming to promote the motherchild binomial health stood out, but five of the nurses revealed being unaware of the Agenda de compromissos para a saúde integral e redução da mortalidade infantil. Conclusion: The health actions performed by the nurses contemplated the guidelines of the Agenda de compromissos para a saúde integral e redução da mortalidade infantil, although the majority of the participants are not aware of the Agenda. doi: http://dx.doi.org/10.5020/18061230.2013.p530